Synthesis of Thieno[2,3-c]pyridine Derivatives by 1,2,3-Triazole-Mediated Metal-Free Denitrogenative Transformation Reaction - Eroglu, Kumsal; Gunkara, Omer Tahir; Dehaen, Wim (WILEY-V C H VERLAG GMBH, 2025)
In this study, we report the synthesis of thieno[2,3-c]pyridine derivatives by a metal-free method via fused 1,2,3-triazoles. In the synthesis of this skeleton using a three-step method, we first obtained 1-(2,2-dimethoxyethyl)-5-(thiophen-2-yl)-1H-1,2,3-triazole through a one-pot triazolation reaction and in the next step, we synthesized the thieno[2,3-c][1,2,3]triazolo[1,5-alpha]pyridine compound using a modified Pomeranz-Fritsch reaction. In the final step, the synthesis of thieno[2,3-c]pyridine derivatives was achieved in good yield via acid-mediated denitrogenative transformation reactions. This mild condition synthetic process has enabled access to the title compounds, of which limited examples have been reported until now in the literature. Thus, the syntheses of 7-(substituted methyl)thieno[2,3-c]pyridine, thieno[2,3-c]pyridine-7-ylmethyl esters, and imidazo[1,5-alpha]thieno[2,3-c]pyridine derivatives have been successfully achieved.
Keywords: 1,2,3-triazoles; metal-free denitrogenative transformation; thieno[2,3-c]pyridine; Chemistry